Effect of nitrogen management on population growth of brown planthopper (Nilaparvata lugens) / Nur Asyiqin Mustafa - Mustafa, Nur Asyiqin (Faculty of Plantation and Agrotechnology, 2019)
Paddy is the important crop and the major sources for people in all country including Malaysia. This plant is very crucial to the people of the world population, which it gives a carbohydrate source beside a staple food grain. Brown Planthopper (Nilarpavata lugens) pest is the main enemy to rice plant. The pest destroyed paddy plant through “hopper burn” symptom and also causing heavy damaged. Present study evaluated that the application of different level of nitrogen (N) is the important factor during the development of phytophagous insect. Beside induced the plant growth, the higher fertilized treatment also favored for BPH development compared to low fertilizes input. Three levels of nitrogen were applied to planting area. 15DAT N (T1=3.5, T2=4.5, T3=5.5, T4=6.5 g/m²), 45 DAT N (T1=3.3, T2=4.3, T3=5.3, T4=6.3 g/m²) and 70 DAT N (T1=3.2, T2=4.2, T3=5.2, T4=6.2 g/m²). The study was conducted under the rain shelter. T1, T2, and T3 has no significant different compare to T4 which has a significant different. Interaction of higher level of nitrogen showed significant effect on population growth of Brown Planthopper. Therefore,fertilization with highest amount of nitrogen will increase the population and number of Brown Planthopper.